Evaluation of the Students' Self-Regulation Skills and Perceived Self-Efficacy in Flipped Classroom and Blended Learning Environments (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2018)
In this study, we aimed to determine the impact of flipped classroom, blended learning and traditional methods on student self-regulation skills and computer self-efficacy perceptions. A total of 119 students constituted the working group of research who are attending Science Education, Turkish Education and Primary Education departments at Kilis 7 Aralık University Muallim Rifat Faculty of Education in the fall term of 2017-2018 academic years. Within the scope of the research, three groups were formed; two of them were experimental and one was control group. Flipped classroom was used in experimental group-I, blended learning method was used in experimental group-II and traditional approach was used in control group. "Computer self-efficacy scale" and "self-regulation scale" have been used for data collection tools which have been applied to the students. Descriptive statistics, t-test and one-way ANOVA were used to analyze the obtained data. There was no significant difference between the computer self-efficacy perceptions and self-regulation skills of the students in experiment-I, experiment-II and control groups after nine weeks of research. It has also been found that the flipped classroom has a positive effect on students' self-regulation skills.